Synthesis of Linear Array Antenna for Required Range of Beam Width Using Optimization Algorithms - Venkateswara rao, N; Challa Ram, G (International Journal of Engineering and Technology, 2018)
In an application like radar there is a need for a wide range of Beam widths depending on whether the radar is operating in search mode or tracking mode. Wide range of beam widths can be achieved by using optimization algorithms like Biogeography-based optimization (BBO) and Differential Evolution Algorithm (DE). The desired beam width should be achieved without any significant increase in the side lobe level (SLL). This can be done by optimizing both SLL and FNBW simultaneously. Synthesis of linear array antenna for a fixed range of beam width is obtained by using the proposed methodology. The results for simultaneous optimization of FNBW and SLL using BBO and DE algorithms are compared.Â Â